2011
DOI: 10.1177/1049732311421681
|View full text |Cite
|
Sign up to set email alerts
|

Registered Nurses Integrate Traditional Chinese Medicine Into the Triage Process

Abstract: People in the United States often consult registered nurses (nurses) for advice when they want to explore alternatives to Western medicine, such as traditional Chinese medicine (TCM). Nurses find themselves confronting dilemmas when they are caught between these radically different worlds of medical cultures and thinking. Twenty Minnesota nurses were interviewed to learn how they integrate TCM into their triage process. Symbolic interactionism was the research framework used, and mixed coding methods facilitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 12 publications
0
10
0
1
Order By: Relevance
“…Due to the conception of acupuncture as a supplement to Western medicine, some participants considered it as an alternative. We found no evidence of the perception that acupuncture could replace Western medicine, but rather that the term alternative was used to refer to the possibility of reinforcing conventional medicine (Bertrand, 2012;Bishop et al, 2012;Hsiao et al, 2006;Schroer et al, 2009).…”
Section: Perceptions Of Acupuncture Among Health Professionalsmentioning
confidence: 72%
See 3 more Smart Citations
“…Due to the conception of acupuncture as a supplement to Western medicine, some participants considered it as an alternative. We found no evidence of the perception that acupuncture could replace Western medicine, but rather that the term alternative was used to refer to the possibility of reinforcing conventional medicine (Bertrand, 2012;Bishop et al, 2012;Hsiao et al, 2006;Schroer et al, 2009).…”
Section: Perceptions Of Acupuncture Among Health Professionalsmentioning
confidence: 72%
“…Acupuncture was also used as support during pregnancy and childbirth (Cant et al, 2011) and before and after surgery (Schiff et al, 2012). Regarding the country of origin, five studies were conducted in the United Kingdom (Adams, 2001;Bishop et al, 2012;Cant et al, 2011;Hughes et al, 2006;Schroer et al, 2009), three in Germany (Joos et al, 2008;Frank and Stollberg, 2004;Berger et al, 2012), two in Norway (Johannessen, 2009(Johannessen, , 2011, two in Australia (Grace and Higgs, 2010;Raynera et al, 2011) and two other studies in the United States (Bertrand, 2012;Hsiao et al, 2006). Israel, Denmark, Canada and Switzerland only provided one study each to this review (Marian et al, 2006;Schiff et al, 2012;Verhoef et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the official data of the year 2009, there were 440.7 thousand different levels of medical service institutions providing TCN, and the data of the year 2011 showed that 1.86 million registered nurses (RN) worked in those institutions [ 9 ]. With the increasing acceptance of TCM in the western countries, nurses in the United States tend to disseminate TCM information and education to patients [ 10 ]. And some overseas nursing schools began to send students to China to learn TCN [ 11 ].…”
Section: Introductionmentioning
confidence: 99%